Using Beetle Drive Game in Teaching Listening for Young Learners - Bimbi Lastri Prima; An Fauzia R. Syafei (Journal of English Language Teaching, 2012)
The special characteristics having by young learners require the teacher to create an atmosphere where children engage to the lesson without forgetting that the children’s world full of joy in teaching English as “Local Content” for young learner in Elementary school. Related to this condition, the proper activity to teach young learners is by having games. One examples of game for teaching listening related to instruction around the classroom in fourth grade of elementary school students is Beetle Drive Game. this game will train students’ ability in listening by giving respond toward the instructions given. The most suitable material for this game is “decorating classroom”. The instructions are  “glue the ornaments, hang the maps, stick the posters, turn left, turn right, go ahead, down, up, below, left and right.”.Karakteristik khusus anak - anak dan kondisi pembelajaran bahasa Inggris di sekolah dasar sebagai muatan lokal,  mengharuskan guru untuk menciptakan  kegiatan pembelajaran yang bisa membuat anak-anak untuk tetap belajar  tanpa melupakan dunia permainan mereka.  Sehubungan dengan hal ini, belajar sambil bermain adalah sebuah kegiatan yang paling cocok untuk digunakan. Salah satu contoh permainan yang bisa digunakan untuk mengajarkan kegiatan mendengar pada pembelajaran bahasa Inggris untuk mengajarkan instruksi – instruksi berkaitan dengan lingkungan kelas di kelas empat SD adalah Beetle Drive Game. Kemampuan mendengar siswa akan dilatih dengan memberikan respon terhadap instruksi-instruksi yang ada dalam permainan ini. Materi ajar yang cocok untuk permainan ini yaitu “decorating classroom dengan instruksi : “glue the ornaments, hang the maps, stick the posters, turn left, turn right, go ahead, down, up, below, left and right.”. Media yang diperlukan adalah“ornaments, posters, map and location map”.   Kata Kunci: Beetle Drive game, Instruction, decorating classroom